Cartilage tympanoplasty for recurrent cholesteatoma using a single sliced cartilage graft: Our experience in 14 ears. Issue 9 (22nd September 2021) - Komori, Masahiro; Kobayashi, Taisuke; Hyodo, Jun; Hyodo, Masamitsu
Abstract: Our procedure may provide a useful alternative in cases where previous surgeries have failed to eradicate the cholesteatoma. Abstract : Our procedure may provide a useful alternative in cases where previous surgeries have failed to eradicate the cholesteatoma.